Influence of thyroid hormones on bone density - Alden Begić; Amela Begić; Ajla Arnautović-Halimić (Medicinski glasnik, 2019)
Aim: To investigate the relations between hormonal status of the thyroid gland and mineral bone density in women in menopause with or without osteoporosis. Methods: The study included 120 postmenopausal women, who were divided into two groups. Group I included postmenopausal patients with osteoporosis, of whom 30 were in the early stages of postmenopause, and 30 of them where in the late postmenopausal phase. The second group included patients with preserved bone mass, of which 30 were in the early stage of postmenopause, and 30 were in the late postmenopausal phase. Bone densitometry (DEXA) was performed for all patients, along with analysis of the level of follicle-stimulating hormone (FSH), thyroid-stimulating hormone (TSH), free thyroxine (FT4), and free triiodothyronine (FT3). Results: A statistically significant correlation between TSH level and mineral bone density in the lumbar spine level (r=0.27) was found in early postmenopausal women (r <0.05), TSH and T-score at the level of the lumbar spine (r=0.31) (p<0.05), as well as between TSH and mineral content of the femur bone (r=0.29; <0.05). There was statistically significant independent association between thyroxine and mineral bone density at the lumbar spine level in the late postmenopausal women (ß=0.29; p=0.025). Conclusion: In the early postmenopausal phase, TSH was associated with mineral bone density in the lumbar spine and in the area of the femur.
Keywords: densitometry; thyroid gland; osteoporosis